VD_FINDINFO Pron / 2012 / 34 vom 28. Februar 2012 - VD Tribunal cantonal (2012)
DÉLAI DE RECOURS, DÉCISION D'IRRECEVABILITÉ, GARDE DU COURRIER, LA POSTE | 273 CC, 420 al. 2 CC, 464 CPC, 489 CPC, 492 al. 2 CPC